Campursari as a Hybrid Music: A Case Study on Three Models of Campursari Music - Wahyudi, Aris; Laksono, Joko Tri; Abdullah, Zolkipli; Sriwulan, Wilma (Resital: Jurnal Seni Pertunjukan, 2024)
Some music researcher state that campursari is a hybrid music. However, this opinion is only based on the combination of diatonic and pentatonic tones. But, Clothier explains, what is meant by hybrid culture is not just a mixture of several types of culture, but there are historical aspects and certain conditions to declare its existence as a hybrid culture. Therefore, this research aims to review the campursari phenomenon to gain clarity its capacity on theoretical. This research is qualitative research using analytical descriptive methods through tracing the history of campursari music. The term campursari appeared around the 1950s when Waljinah performed the “Kembang Kacang” song in keroncong music. This song was adopted from Javanese musical compositions, and then developed until now. in terms of major genres, campursari music consists of three models, there are Waljinah (keroncong), Manthou’s (Javanese musical/pentatonic), and Didi Kempot (Western/diatonic music). Through the case of the “Kembang Kacang” song which was analyzed by the hybrid cultural theory of Bhaba, Livenson, and Clothier and combined with Titon’s theory, it was concluded that the Waljinah model campursari is first derivative (F1), the Manthou’s model campursari is true hybrid music (pure strain), while the other model of campursari called “gedanken” hybrid.